M2 differentiation of MonoMac‐1 cell line induced by M‐CSF and glucocorticoid pathways. Issue 10 (13th February 2020) - Vakili, Sarah; Fischer, Tracy; Rappaport, Jay
Abstract: Models of macrophage subtypes require molecular characterization to reliably facilitate their differentiation. Although CD16 + (Fc‐gamma III receptor) monocytes that express CD163 (a hemoglobin/haptoglobin receptor) have been implicated in a variety of disease states, the conditions necessary to establish lineages of these cell subtypes remains unknown. The current investigations utilize a cell line derived from acute myelogenous leukemia lineage, MonoMac‐1, to interrogate the factors that promote the development of CD16 + macrophages that express CD163. Results implicate the glucocorticoid pathway as well as c‐fms signaling based on the action of dexamethasone and macrophage colony‐stimulating factor‐1 in promoting CD16 + expression, in addition to phorbol myristate acetate and lipopolysaccharides treatment. The ability of glucocorticoid and c‐fms receptor antagonists to inhibit CD16 + cell formation further establishes the role of these pathways in CD16 expression in this cell line. In view of the inherent difficulty in working with primary cells as well as donor variation, cell lines may be preferable to primary cells for their consistency. We envision that the process we use to induce CD16 expression in this cell type will be useful for screening and identification of drug candidates potentially useful for the treatment of diseases where the etiology involves the expansion of the CD16 + monocytes subset or the accumulation of CD163 + tissue macrophages. Abstract : This manuscript describes a methodology to differentiate monoMac1 cells such that the cells express CD163 and CD16, markers of M2 polarization. Our results implicate c‐fms signaling and the glucocorticoid pathway.